A Genomic Sample Sequence of the Entomopathogenic Bacterium Photorhabdus luminescens W14: Potential Implications for Virulence - Ffrench-Constant, Richard H. (American Society for Microbiology, 2000)
Photorhabdus luminescens is a pathogenic bacterium that lives in the guts of insect-pathogenic nematodes. After invasion of an insect host by a nematode, bacteria are released from the nematode gut and help kill the insect, in which both the bacteria and the nematodes subsequently replicate. However, the bacterial virulence factors associated with this “symbiosis of pathogens” remain largely obscure. In order to identify genes encoding potential virulence factors, we performed ∼2,000 random sequencing reads from a P. luminescens W14 genomic library. We then compared the sequences obtained to sequences in existing gene databases and to the Escherichia coli K-12 genome sequence. Here we describe the different classes of potential virulence factors found. These factors include genes that putatively encode Tc insecticidal toxin complexes, Rtx-like toxins, proteases and lipases, colicin and pyocins, and various antibiotics. They also include a diverse array of secretion (e.g., type III), iron uptake, and lipopolysaccharide production systems. We speculate on the potential functions of each of these gene classes in insect infection and also examine the extent to which the invertebrate pathogen P. luminescens shares potential antivertebrate virulence factors. The implications for understanding both the biology of this insect pathogen and links between the evolution of vertebrate virulence factors and the evolution of invertebrate virulence factors are discussed.